Original and diffracted transition radiation for diagnostics of relativistic electron beams; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 145, Iss. 1-2 - Kaplin V. V. Valery Viktorovich (1998, 1998)
Title screen